Are precipitation concentration and intensity changing in Bangladesh overtimes? Analysis of the possible causes of changes in precipitation systems - Rahman, Md. Siddiqur; Islam, Abu Reza Md. Towfiqul (The Science of the total environment, 2019)
A comprehensive understanding of the changing behaviors of precipitation concentration and intensity plays a pivotal role in water resource management. Hence, we investigated the spatiotemporal changing behaviors of frequency and intensity of 13 precipitation indices and their probable causes of changes in precipitation systems. This study used daily precipitation datasets from 23 sites in Bangladesh and six atmospheric circulation indices during 1975–2017. The results showed that the precipitation concentration index (LCI) varies between 0.57 and 0.63, and the highest value was found in the southeastern region. The precipitation days frequency indices such as AD, LPD, MPD, HPD, and WPD have significantly increased in Bangladesh while precipitation intensity indices such as AII, LPI, MPI, HPI, and WPI have significantly declined; all types of indices have clear rapid changes. The results of detrended fluctuation analysis (DFA) exhibit long-term correlations among all precipitation indices, suggesting that these indices will sustain their present trend line in the upcoming period. The Sunspot (SS) and East Asian Summer Monsoon Index (EASMI) had a negative influence on ACI and South Asian Summer Monsoon index (SASMI) had a strong positive influence on precipitation days frequency indices. The significance analysis using the random forest (RF) algorithm showed that SS is the largest contributing factor affecting the precipitation systems in Bangladesh. ECMWF ERA5 reanalysis datasets revealed that elevating summer geopotential height, higher anticyclonic anomaly, increasing low and decreasing high cloud covers and lower solar radiation with adequate moisture divergence fluxes contributed to variations in precipitation extremes in Bangladesh. Linear trend of Arid days, AD (a), Sequential Mann-kendall test to detect rapid change (b), DFA long term forecasting of ACI (c) and Cross wavelet between SASMI and ACI (d). [Display omitted] •Concentration index (LCI) vary between 0.57 and 0.63. The highest value was in southeastern part and the lowest LCI value was in eastern part.•Precipitation days frequency indices significantly increased, whereas precipitation intensity indices significantly decreased.•Sunspot is the most important factor influencing the precipitation systems using the RF model.•SS and EASMI had negative (or positive) impacts, while SASMI had positive (or negative) effect on most precipitation indices.